2015
DOI: 10.5772/61395
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Dependent Strain Distributions of Au and Ag Nanoparticles in a Metal-Oxide-Semiconductor-Based Nonvolatile Memory Device

Abstract: The matrix-dependent strain distributions of Au and Ag nanoparticles in a metal-oxide-semiconductor based nonvolatile memory device are investigated by finite element calculations. The simulation results clearly indicate that both Au and Ag nanoparticles incur compressive strain by high-k Al 2 O 3 and conventional SiO 2 dielectrics. The strain distribution of nanoparticles is closely related to the surrounding matrix. Nanoparticles embedded in different matrices experience different compressive stresses, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…also investigate the matrix‐dependent strain distribution of different metal NPs embedded in dielectric layers with various thickness, which is sandwiched between Al 2 O 3 and SiO 2 as blocking and tunneling oxide layer, respectively. [ 77 ] Since strong compressive strain existed in the NPs, strain‐relaxing defects serving as charge storage centers would be created at the surface of Au or Ag NPs, leading to capture more charges and enhance charge storage properties. This research showed that compare to Au or Ag NPs in the SiO 2 matrix, metal nanoparticles in the Al 2 O 3 matrix store more charges, especially for gold.…”
Section: Approaches To Synthesize Metal Nps Layermentioning
confidence: 99%
“…also investigate the matrix‐dependent strain distribution of different metal NPs embedded in dielectric layers with various thickness, which is sandwiched between Al 2 O 3 and SiO 2 as blocking and tunneling oxide layer, respectively. [ 77 ] Since strong compressive strain existed in the NPs, strain‐relaxing defects serving as charge storage centers would be created at the surface of Au or Ag NPs, leading to capture more charges and enhance charge storage properties. This research showed that compare to Au or Ag NPs in the SiO 2 matrix, metal nanoparticles in the Al 2 O 3 matrix store more charges, especially for gold.…”
Section: Approaches To Synthesize Metal Nps Layermentioning
confidence: 99%